2015
DOI: 10.20518/thsd.61635
|View full text |Cite
|
Sign up to set email alerts
|

Şanlıurfa'da birinci basamak sağlık hizmetleri çalışanlarının Ulusal Kanser Tarama Standartları ile ilgili bilgi düzeyi

Abstract: Amaç: Araştırma, Şanlıurfa Halk Sağlığı Müdürlüğü'ne bağlı aile sağlığı merkezleri (ASM) ve toplum sağlığı merkezlerinde (TSM) çalışan sağlık çalışanlarının Ulusal Kanser Tarama Standartları (UKTS) hakkındaki bilgi düzeyini değerlendirmek amacıyla yapılmıştır. Yöntem: Araştırma kesitsel tiptedir. Araştırmanın evrenini, Şanlıurfa'da ASM ve TSM lerde çalışan 1019 sağlık çalışanı (hekim ve hekim dışı) oluşturmuş; araştırmaya 776 kişi katılmıştır. Araştırma verisi, yapılandırılmış bir anket ile yüz yüze görüşülere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
0
0
0
1
Order By: Relevance
“…In the same study, the level of knowledge about screening was found to be higher in those who received training. [17] According to the literature and our study results, in order for screening programs to be successful, periodic trainings and meetings should be organized, with emphasis on the areas in which physicians and healthcare professionals working in the field are deficient.…”
Section: Discussionmentioning
confidence: 97%
“…In the same study, the level of knowledge about screening was found to be higher in those who received training. [17] According to the literature and our study results, in order for screening programs to be successful, periodic trainings and meetings should be organized, with emphasis on the areas in which physicians and healthcare professionals working in the field are deficient.…”
Section: Discussionmentioning
confidence: 97%
“…Nitekim 2015 tarihli bir çalışmada birinci basamak sağlık çalışanlarının ulusal tarama programları ile ilgili bilgilerinin istenilen seviyede olmadığı gösterilmiştir. 25 Öte yandan Niğde'nin içinde bulunduğu coğrafi bölgede HPV pozitiflik oranı %3.2 iken, benzer tarihlerde Niğde özelinde %5.5 olarak tespit edilmiştir. 21 Niğde'de bölge ortalamasından neredeyse iki kat daha fazla HPV pozitiflik oranı mevcuttur.…”
Section: Discussionunclassified